2007
DOI: 10.1111/j.1365-2133.2007.07909.x
|View full text |Cite
|
Sign up to set email alerts
|

Naevus sebaceus on the female breast accompanied with a tubular apocrine adenoma and a syringocystadenoma papilliferum

Abstract: 401. 7 Miller JJ. Relaxer-induced alopecia. Am J Contact Dermat 2001; 12:238-9. 8 Sperling LC, Sau P. The follicular degeneration syndrome in black patients. 'Hot comb alopecia' revisited and revised. Arch Dermatol 1992; 128:68-74. 9 Sperling LC. Scarring alopecia and the dermatopathologist. J Cutan Pathol 2001; 28:333-42. 10 Keita S, Faye O, Kane BD et al. Hair care and hair styles in women in Bamako, Mali. Int J Dermatol 2005; 44 (Suppl. 1):26-9.Conflicts of interest: none declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, the immunohistochemical studies in our case were positive for GCDFP-15 in the TAA lesion, but they were negative in the SCAP lesion. These findings further support the biological differences between the TAA and SCAP apocrine-differentiated tumor, as Yamane et al 10 suggested.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the immunohistochemical studies in our case were positive for GCDFP-15 in the TAA lesion, but they were negative in the SCAP lesion. These findings further support the biological differences between the TAA and SCAP apocrine-differentiated tumor, as Yamane et al 10 suggested.…”
Section: Discussionsupporting
confidence: 85%
“…Ishiko et al 6 suggested that TAA and SCAP occurred together only when they were preceded by an organoid nevus. Five cases of TAA and SCAP were reported to be associated with NS [4][5][6]8,10 . However, Lee et al 9 reported 1 case in the external auditory canal that had no evidence of pre-existing NS.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The finding of a tubular apocrine adenoma in a female of middle age in our case is in concordance with what others have reported. [1][2][3][4][5][6][7]10,12,[14][15][16][17][18] Tubular apocrine adenoma is found most commonly on the scalp but lesions have also been described at a variety of other sites including the face, [6] eyelid, [18] axilla, [3] leg and genitalia. [4,11,17] However, Lee et al reported a case in the external auditory canal.…”
Section: Discussionmentioning
confidence: 99%
“…In 40% of reported cases, the patient also had a nevus sebaceous and/or syringocystadenoma papilliferum but in our case no such associated tumor was found. [10][11][12][13][14][15] The tubular apocrine adenoma is benign in nature and recurrence following excision is uncommon. Theories regarding the origin of the tumor have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 145 cases of SCAP reviewed by Mammino and Vidmar, 1 40% occurred with NS and 9% with basal cell carcinoma. But, it occasionally coexists with other tumors such as apocrine hidrocystoma and clear cell syringoma, 24 tubular apocrine adenoma, [25][26][27][28] apocrine poroma, 29 carcinoma, 32 mixed tubulopapillary hidradenoma, 33 hidradenoma papilliferum, 34 trichilemmoma, 35 apocrine hidrocystoma, 36 giant comedo, 37 condyloma acuminatum, 5,38 and verrucous carcinoma. 39 SCAP that is not associated with NS frequently appears hyperkeratotic or verrucous.…”
Section: Case Reportmentioning
confidence: 94%